Optimising conditions for bioethanol production from rice husk and rice straw: effects of pre-treatment on liquor composition and fermentation inhibitors - Jia Wu; Adam Elliston; Gwenaelle Le Gall; Ian J. Colquhoun; Samuel R. A. Collins; Ian P. Wood; Jo Dicks; Ian N. Roberts; Keith W. Waldron (Biotechnology for Biofuels, 2018)
Abstract Background Rice straw and husk are globally significant sources of cellulose-rich biomass and there is great interest in converting them to bioethanol. However, rice husk is reportedly much more recalcitrant than rice straw and produces larger quantities of fermentation inhibitors. The aim of this study was to explore the underlying differences between rice straw and rice husk with reference to the composition of the pre-treatment liquors and their impacts on saccharification and fermentation. This has been carried out by developing quantitative NMR screening methods. Results Air-dried rice husk and rice straw from the same cultivar were used as substrates. Carbohydrate compositions were similar, whereas lignin contents differed significantly (husk: 35.3% w/w of raw material; straw 22.1% w/w of raw material). Substrates were hydrothermally pre-treated with high-pressure microwave processing across a wide range of severities. 25 compounds were identified from the liquors of both pre-treated rice husk and rice straw. However, the quantities of compounds differed between the two substrates. Fermentation inhibitors such as 5-HMF and 2-FA were highest in husk liquors, and formic acid was higher in straw liquors. At a pre-treatment severity of 3.65, twice as much ethanol was produced from rice straw (14.22% dry weight of substrate) compared with the yield from rice husk (7.55% dry weight of substrate). Above severities of 5, fermentation was inhibited in both straw and husk. In addition to inhibitors, high levels of cellulase-inhibiting xylo-oligomers and xylose were found and at much higher concentrations in rice husk liquor. At low severities, organic acids and related intracellular metabolites were released into the liquor. Conclusions Rice husk recalcitrance to saccharification is probably due to the much higher levels of lignin and, from other studies, likely high levels of silica. Therefore, if highly polluting chemical pre-treatments and multi-step biorefining processes are to be avoided, rice husk may need to be improved through selective breeding strategies, although more careful control of pre-treatment may be sufficient to reduce the levels of fermentation inhibitors, e.g. through steam explosion-induced volatilisation. For rice straw, pre-treating at severities of between 3.65 and 4.25 would give a glucose yield of between 37.5 and 40% (w/DW, dry weight of the substrate) close to the theoretical yield of 44.1% w/DW, and an insignificant yield of total inhibitors.